TINGKAT LITERASI MEDIA BERBASIS KOMPETENSI INDIVIDU PADA GENERASI MUDA KAHAYYA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
This study aims to measure the level of individual competence-based media literacy among young people in Kahayya Village. The aspects measured include technical skills in utilizing media, critical understanding in evaluating media content, and communicative skills in interacting through media. This study employs a quantitative approach with a descriptive design. The sample consists of 70 young people aged 18–25 years in Kahayya Village, selected using a saturated sampling technique. Data collection was conducted through a questionnaire adapted from the European Commission's Individual Competence Framework. The results indicate that the level of media literacy among young people in Kahayya Village is at a medium level (103.17%). Specifically, the cumulative score for the technical skills variable reached 97.31%, the critical understanding variable was 101.14%, and the communicative skills variable was 111.07%. These findings suggest that young people in Kahayya Village possess adequate competence in operating various media platforms, critically understanding and analyzing media content, and actively participating in media production and utilization for communication and social networking purposes.